Efecto de los diluyentes Ley-Leygo y Triladyl y de dos tiempos de equilibrio en la congelación de semen de verraco - Reyes-González, Erika Abigail (2022)
The aim of this study was to evaluate the effect of Ley-Leygo and Triladyl® extenders and two equilibrium times on individual motility (IM), plasma membrane integrity (PMI), mitochondrial activity (MA) and intact acrosome (IA) in frozen-thawed boar semen. A rich fraction of a total of 20 ejaculates from five boars of a commercial line was used. All ejaculates had a minimum of 80% motility and 85% normal spermatozoa. Each ejaculate was divided into four aliquots: Ley-Leygo and Triladyl® extenders and two equilibrium times (0 and 1 h). The semen samples were thawed at 37 °C for 20 s. The results of the IM and the PMI did not have significant effects for the factors evaluated (p>0.05). There was a significant difference for MA (p<0.05) between the Ley-Leygo (43.57%) and Triladyl® (51.7%) diluents. The IA was 46% for Ley-Leygo and 25% for Triladyl® (p<0.05). The percentage of IA with the equilibration time of 1 h was greater than that of 0 h (p<0.05). It is concluded that the Triladyl® diluent improved the MA and the equilibration time of 1 h improved the percentage of IA.